FRELST OG REDDET FRA AIDS?: Unge pigers håndtering af risikoen for hiv i det sydvestlige Uganda - Wimberley, Kristina (Tidsskriftet Antropologi, 1996)
Kristina Wimberley: Saved from AIDS? The Manoeuvres of Adolescent Giris in Relation to the Risk of HIV in Southwestern Uganda This articles discusses the representation of adolescent giris in the literature on AIDS and in AIDS interventions. In these contexts an image is created of adolescent giris as passive victims of a static inequality in societies pervaded by patriarchy, and as driven by economic want. On the basis of fieldwork material from Ankole, southwestern Uganda, the articles discusses the meaning of “being saved” for adolescent giris in relation to the risk of HIV. For the giris concemed, “being saved” is characterized by conversion to a new lifestyle in which they are virtuous, honest, kind, and above all: avoid and reject men. However, at some point even saved giris enter into relationships with men. In this situation, the giris may find it advantageous to continue to be “really saved” in certain contexts. From the analysis put forward here it emerges that “being saved” as a form of discourse and action enables giris to create a room for manoeuvre that empowers them to tackle the dangers they face - including HIV/AIDS. This agency emerges in the interplay of, on the one hand the constraining and enabling effects of the various life worlds of giris in Ankole, and on the other hand the way in which gendered identities and relationships are negotiated in everyday life between giris and men, as well as among the giris themselves. It is concluded that the standard analysis of giris’ vulnerability in relation to the risk of HIV/AIDS could benefit from an actor-oriented approach that encompasses the interplay between structure and process. An analysis of this kind may reveal the agency of giris, and not exclusively in relation to economic want. This focus on agency could be a point of departure for more effective HIV/AIDS interventions.